A modified homogeneous-heterogeneous reactions for MHD stagnation flow with viscous dissipation and Joule heating. (October 2017) - Khan, Muhammad Imran; Hayat, Tasawar; Khan, Muhammad Ijaz; Alsaedi, Ahmed
Highlights: Magnetohydrodynamic flow of Casson fluid over a stretched surface is considered. Homogeneous-heterogeneous reaction effect is taken into account. Concentration profile enhances with an increase in heterogeneous parameter. Numerical simulation is developed for solution of nonlinear partial differential equations. Abstract: Our objective here is to introduce the new chemical reaction model in MHD stagnation point flow. Mathematical modeling is based for the rheological relations of Casson liquid. Flow induced is due to sheet moving with nonlinear velocity. The velocity of external flow is also nonlinear. Effects of magnetohydrodynamics (MHD), viscous dissipation and Joule heating are also accounted. Nonlinear differential systems via implementation of appropriate transformations are computed through built in shooting method. Graphical and tabular behaviors of various pertinent parameters on velocity, temperature, concentration, skin friction and Nusselt and Sherwood numbers are analyzed. Our computed results interpret that velocity distribution decays for higher estimation of magnetic parameter while temperature distribution shows increasing behavior for larger homogeneous heat parameter.